Pengetahuan Ibu Tentang Tumbuh Kembang Anak Umur 1-3 Tahun di Masa Pandemi Covid 19 - Ina Kuswanti; Lusa Rochmawati; Lisa Rahmawati (Jurnal Indonesia Sehat, 2022)
Background : In Indonesia, 2019 shows that 11.77% of children are still living below the poverty line, which prevents children from getting good nutrition, higher education, decent housing, a friendly environment, and so on. According to DINKES DIY from 2016 mothers must know the process and stages of growth and development in their children, this is because deviations in growth and development in children will occur rapidly when children are 1-3 years old. Purposes: To determine the mother's level of knowledge about the growth and development of children aged 1-3 years. Method: This research is a quantitative research using a cross sectional approach. The population in this study were all mothers who had children aged 1-3 years in Srimartani Village, Piyungan District, Bantul Regency, Yogyakarta Special Region in 2021, amounting to 64 people. The sampling technique used is Simple Random Sampling. The data analysis used is univariate analysis by calculating the percentage distribution of the frequency distribution of the research variables. Result: Of the 18 mothers of children aged 1-3 years studied, it was found that 5 mothers or 27.7% had less knowledge, 7 mothers or 38.8% had sufficient knowledge and 6 mothers or 33 had good knowledge. 3%. Conclusion: Most of the mother's knowledge about child development is sufficient.